The Utilization of Narrative Text to Quantify Elementary School Students' Reading Comprehension Ability - Rohman, Yusuf Abdul; Hartati, Tatat (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
Reading comprehension ability in elementary school is crucial for students, in contrary with that low reading comprehension skills and low student learning outcomes are the main problem. This research aims to analyze the reading comprehension abilities of elementary school students using narrative text. The research method used was a mixed method (quantitative and qualitative) with a sample of 30 elementary school students. The data collection technique used tests and interviews. The research results showed that (1) students' ability to grasp the content of narrative text reading accurately obtained an average of 39%, (2) students' ability to grasp implied and explicit meanings accurately obtained an average of 24%, (3) the ability to conclude correctly obtained an average of 24 %, and (4) students' reading habits were obtained, six of seven samples interested in reading, school books and type of fiction (comics and fables) were the sample choices, five of the seven samples could fully understand all words in text and reading comprehension for two of them depending on the type of text read. Further prospect of this research to become a starting point for future research and a specific illustration for stakeholders in deciding literacy policies for elementary school students